Molluscan Radiation : Lesser-Known Branches - Southward, Alan J. (Advances in marine biology, 2002)
Volume 42 is a thematic volume with reviews on the biology of four major molluscs. Advances in Marine Biology was first published in 1963. Now edited by A.J. Southward (Marine Biological Association, UK), P.A. Tyler (Southampton Oceanography Association, UK), C.M. Young (Harbor Branch Oceanographic Institution, USA) and L.A. Fuiman (University of Texas, USA), the serial publishes in-depth and up-to-date reviews on a wide range of topics which will appeal to postgraduates and researchers in marine biology, fisheries science, ecology, zoology, oceanography. Eclectic volumes in the series are supplemented by thematic volumes on such topics as The Biology of Calanoid Copepods. Advances in Marine Biology is now No. 1 in the highly competitive category of Marine & Freshwater Biology. The 2000 journals citation report from the Institute for Scientific Information shows that Advances in Marine Biology has an Impact Factor of 3.37, the highest in the field. Key Features * AMB first published 1963 * This volume presnts a selection of reviews on the biology of lesser-known taxa of the phylum Mollusca, including: * The mostly diminutive protobranch bivalves * The slug-like shelled opisthobranchs * The highly specialized and evolutionarily advanced * Tusk shells * The beautiful, priceless, yet frustratingly hard-to-collect slit shells.